2019
DOI: 10.1002/hpm.2824
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the health behaviors of elderly individuals and influencing factors: Evidence from the ChineseLongitudinalHealthyLongevitySurvey

Abstract: Summary Introduction Health behaviors play an important role in determining individual health status; thus, understanding differences in the health behaviors of elderly individuals and their influencing factors is a prerequisite for the formulation and implementation of health behavior promotion policies for elderly individuals. The objectives of this study were to explore differences in health behaviors among Chinese elderly people and their influencing factors. Methods Based on data from the Chinese Longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
2
12
0
2
Order By: Relevance
“…The six options are "married and living with a spouse, " "married but temporarily not living with the spouse for work and other reasons, " "separated, no longer living together as a spouse, " "divorced, " "widowed, " and "never married, " the first three options are reclassified into "married" and the last are reclassified into "single." Previous studies (Erpeng Liu) have pointed out that smoking and drinking will have an impact on health as unhealthy lifestyles (32). Meanwhile, physical exercise is also one of the factors affecting health.…”
Section: Variable Descriptionmentioning
confidence: 99%
“…The six options are "married and living with a spouse, " "married but temporarily not living with the spouse for work and other reasons, " "separated, no longer living together as a spouse, " "divorced, " "widowed, " and "never married, " the first three options are reclassified into "married" and the last are reclassified into "single." Previous studies (Erpeng Liu) have pointed out that smoking and drinking will have an impact on health as unhealthy lifestyles (32). Meanwhile, physical exercise is also one of the factors affecting health.…”
Section: Variable Descriptionmentioning
confidence: 99%
“…11.15.28.30.32 Liu ve ark. 32 tarafından yapılan çalışmada yaş arttıkça sağlıklı yaşam biçimi davranışlarının arttığı saptanmıştır. Çalışmada literatüre benzer olarak sağlıklı yaşam biçimi davranışları arasında fiziksel aktivite alt boyutunun en düşük puana sahip olduğu 14,33 göz önüne alındığında, ilerleyen yaş ile birlikte kronik hastalıkların ve fonksiyonel yetersizliklerin artması ile sağlıklı yaşam biçimi davranışlarının azalabileceği öngörülmektedir.…”
Section: Araştırmanın Modeliunclassified
“…Benzer olarak literatürde gelir düzeyindeki artışın sağlıklı yaşam biçimi davranışlarını olumlu yönde etkilediği bildirilmektedir. 12,13,32 Son ve ark. 35…”
Section: Araştırmanın Modeliunclassified
“…Before liberation and on the early Days of New China, early marriage was common in Chinese society and might have an important role on late-life marital instability. Furthermore, a current study reported that the majority of the health behaviors of elderly individuals in China were not healthy [32].…”
Section: Introductionmentioning
confidence: 67%